Tingkat Pengetahuan tentang Sindrom Premenstruasi dan Penanganan Sindrom Premenstruasi - Sherley Puspitasari N.F; Dyah Suryani (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2020)
Background: Adolescence is a period of a child turned into an adult. Adolescence women two yearsearlier than men. Data pornography, the adolescent is a large population than the population of theword. WHO and some other word body called on all countries of Southeast Asia to provide itscommitment to observe and protect the needs of adolescents and information, skills, service, and safeenvironment and supportive of essential reproductive health. The reproductive period in the life of awoman who started from menarche until menopause occurs. The menstrual period they aresometimes accompanied by disturbances such as premenstrual syndrome (PMS). It is estimated that80-10% of women do not have PMS, and approximately 25-40% have PMS. Most women experiencePMS symptoms in a long period. The symptoms are of an emotional outburst in the form of anger,high sensitivity, sad, lonely, until the desire to commit suicide. Is research target is to know therelation of between level of knowledge of syndrome premenstrual with the handling of syndromepremenstrual of at adolescent of age 12-15 year in SMP PGRI Bantul.Methods: The study was observational analytic with the cross-sectional approach. The samples wereall students SMP PGRI Bantul amounting to 138 students and measuring the level of knowledge andhandling of premenstrual syndrome using questioner. Analysis of data used univariate and bivariateanalysis with chi-square.Result: There was a relationship between the level of knowledge about premenstrual syndrome withthe handling of premenstrual syndrome in adolescents age 12-15 years in the SMP PGRI Bantul withthe value of P=0,000.Conclusion: There was a relationship between the level of knowledge about premenstrual syndromewith the handling of premenstrual syndrome treatment.Key words: level of knowledge, premenstrual syndrome, adolescent